Types and Localization of Abdominal Adhesions after Open Operations (Experimental Study) - F.T. Akhmedov (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2022)
There is a great need for more efficient and more widely used preventive treatment of post-operative abdominal adhesions. Objective - to study the type of adhesions in the abdominal cavity after open operations in the experiment. Materials and methods. The study was conducted on 90 white outbred rats divided into three groups. We mechanically damaged the surface of the small bowel segment in all rats. The control group (group 1) included 30 rats not administered any drugs into the abdominal cavity after the small bowel segment damage. The comparison group (group 2) consisted of 30 rats, which were introduced one mL of mezogel. The study group comprised 30 rats, which were administered a 1 mL mixture of metronidazole, dextran, contrykal (in a ratio of 1:1:0.1, respectively) + O2 into the abdominal cavity; the wound of the latter was closed using a layered suture technique. On days 5, 10 and 21, the tissues taken from the suture site, peritoneum, damaged small bowel segment, liver, and omentum were analysed histologically. Results. On day 10 in groups 1 and 2, compared to day 5, the proportion of filmy adhesions decreased by 45.9% (p=0.004), but the proportion of dense adhesions increased by 64.7%. The comparative between-group analysis on day 5 in groups 1 and 2 revealed no difference in the proportion of filmy adhesions, whereas in group 3 the proportion of filmy adhesions was 4% higher and the proportion of dense adhesions was 16.5% lower. Planar adhesions predominated in all groups. Conclusions. There were more filmy adhesions seen on day 1, and the complete dense adhesion formation was observed by day 21. Planar adhesions predominated (54.5 - 60.0%). The area of postoperative sutures was involved in the adhesion formation. The adhesions in the sutures - peritoneum area as well as the omental adhesions were detected in all animals. Introduction of drugs, mezogel or a mixture of metronidazole, dextran, contrykal + O2, into the abdominal cavity contributed to the reduction of adhesions between the small bowel loops. The experiments with laboratory animals were provided in accordance with all bioethical norms and guidelines. No conflict of interests was declared by the author.